A Potential Concept In The Management of Tumors With Modulation of Prostaglandin, Nitric Oxide and Antioxidants. (2007) - Al-Waili, Noori S.
Abstract : Prostaglandins (PGs), nitric oxide (NO), free radicals and chronic inflammation play a major role in tumorogenesis. We have found in vivo that PGs suppress antibody production; reduce serum iron, and modulate bone marrow function. Tumors are associated with immunosuppression and anemia. We have hypothesized that the over-production of PGs is responsible for immunosuppression and anemia in conditions associated with increased production of PG such as tumor, and that PG inhibitors might help reversing immunosuppression and anemia, and play a role in eradication and prevention of tumors. This is supported by reports that demonstrate the immunosuppressive effects of PGs in tumors. PG inhibitors have also been shown to be crucial in the prevention of tumors such as esophageal and colon cancers. Others and we have found that high NO production was encountered in patients with cancer while antioxidants are decreased. Evidence supports the efficacy of PG inhibition in malignancies, and the concept of PG inhibition, NO modulation, anti-oxidants, immunotherapy with antibody or immune cells, and anti-inflammatory agents when used in the prevention and management of malignancies are discussed.